2017
DOI: 10.1158/1538-7445.am2017-2629
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2629: The synergy between BXCL701, a DPP inhibitor, and immune checkpoint inhibitors discovered using AI and Big Data analytics

Abstract: Using the proprietary Big Data PharmGPS® Discovery platform, BioXcel has created a comprehensive relationship map between immune-evasion and immune-activation pathways, comprising interacting genes and all overlapping pharmacological agents and tumors. This map was used to identify clinically validated compounds that would act synergistically in combination with immune-checkpoint inhibitors (ICI) by remodelling the tumor micro-enviroment and transforming cold, non-inflamed tumors into hot immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, these studies demonstrated no to minimal clinical effect of talabostat and phase 3 studies of talabostat in NSCLC were put on hold. Today, the compound has regained interest, especially in combination therapy in pancreatic and neuroendocrine prostate cancer (Rastelli et al, 2017(Rastelli et al, , 2018 and in AML as stated above. Also other pan-inhibitors of the DPPs have been studied in cancer (Duncan et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, these studies demonstrated no to minimal clinical effect of talabostat and phase 3 studies of talabostat in NSCLC were put on hold. Today, the compound has regained interest, especially in combination therapy in pancreatic and neuroendocrine prostate cancer (Rastelli et al, 2017(Rastelli et al, , 2018 and in AML as stated above. Also other pan-inhibitors of the DPPs have been studied in cancer (Duncan et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Today, this field has regained the interest of researchers. Recently, the combination of BXCL701 and immune checkpoint inhibitors has been reported to exert synergistic antitumor effects in syngeneic pancreatic ductal adenocarcinoma models [33,34]. In a mouse model of pancreatic cancer, the triple therapy of BXCL701, NKTR-214, and PD-1 inhibitor achieved tumor regression in all mice [35].…”
Section: Discussionmentioning
confidence: 99%